DIAGNOSTIC EFFICIENCY OF MULTIDETECTOR COMPUTED TOMOGRAPHY IN PATIENTS WITH TONGUE CANCER - V. E. Sinitsyn; V. S. Petrovichev; P. V. Vasil'ev; E. A. Mershina (Вестник рентгенологии и радиологии)
Objective: to determine the capacities of multidetector computed tomography (MDCT) to diagnose tongue cancer.Material and methods. Intravenous bolus contrast-enhanced MDCT was performed in 40 patients with tongue cancer diagnosed during complex clinical and instrumental examination. In all cases, the tumor had a structure of squamous cell carcinoma of varying grades. The results of MSCT were compared with the data of surgery and cytological and histological examinations. Tongue tumor accumulation of a contrast agent was qualitatively analyzed.Results. In 38 (85%) patients, the tongue tumor actively accumulated the contrast agent and was clearly differentiated in the presence of unaffected portions of the tongue and other adjacent anatomical structures, such as mouth floor, oropharynx, and larynx. Only in two cases, the tumor failed to significantly accumulate the contrast agent, which was associated with that there were massive decay areas in its structure. The sensitivity, specificity, and accuracy of MDCT in the diagnosis of tongue cancer were 95, 80, and 87.5%, respectively. MDCT could reliably differentiate changes in tongue cancer from non-tumor diseases. The result of constructing the curve of diagnostic errors became the following values: the area under the curve was 0.875 and the P-value (Asymptotic Sig.) was 0.0001.Conclusion. Intravenous bolus contrast-enhanced MDCT has a high diagnostic efficiency in identifying tongue cancer. The technique can establish the location of a tumor and to reveal the extent of the process to the nearby organs.